Intervención fisioterapéutica en el accidente cerebro vascular con secuela de hemiplejia en pacientes que acuden al área de rehabilitación física del Hospital Martín Icaza Cantón Babahoyo. Noviembre 2023 - abril 2024. - Cayambe Ases, Johanna Margoth (2024)
A cerebrovascular accident (CVA) is a neurological pathology that occupies third place in deaths worldwide and first in disability, especially after the age of 30. This pathological condition occurs due to a decrease in blood flow to a certain area of the brain. The present study will serve to expand information on the definition of stroke, types, causes, risk factors and prevention, in the same way, establish the physiotherapeutic intervention, physiotherapeutic procedures, actions and assessment scales used in patients with stroke with sequelae of hemiplegia, who attend the Martin Icaza Hospital of the Babahoyo Canton, in the period November 2023 - April 2024. In terms of methodology, the research design follows a mixed and non-experimental approach. Regarding the techniques, the open interview with the physiotherapists in charge was used; survey aimed at patients and/or family members. To carry out the sampling, a sample of 25 patients with stroke with sequelae of hemiplegia was selected, in order to achieve the objectives set out above. Through data collection techniques, information was collected where positive results were obtained in relation to the procedures applied in stroke since the patients expressed an improvement in their independence. It should be emphasized that it is important to emphasize the prevention of this pathology and that physiotherapy intervention in stroke is a long-term treatment, which is why it is essential to have the support of family members and a multidisciplinary team.